Financial inclusion, regulation, financial literacy, and financial education in Armenia - Armen Nurbekyan; Naneh Hovanessian (Asian Development Bank Institute (ADBI), 2018)
Financial inclusion has significantly advanced in Armenia during the last decade. Rural and urban areas, however, have benefited unevenly. The high cost of providing financial services, the lack of physical infrastructure, higher poverty rates, and the low level of financial literacy are the main barriers to financial inclusion in the rural areas. The availability of, and the high level of trust in, postal services in all villages, along with innovative technologies, should be exploited to address the inadequate physical infrastructure. Insurance services, in particular health and agriculture insurance, have a high growth potential. Mandatory health insurance along with an e-health infrastructure can boost high-quality financial inclusion. Targeted financial education policies addressing the most vulnerable groups, in particular the rural population and the unemployed, will significantly increase the quality of financial inclusion. Addressing data gaps, especially in the SME sector, should be a priority for policy makers. Overall, a clear separation of strategies for financial inclusion from the National Strategy for Financial Education clarifying quantitative goals and policies will be beneficial.
Keywords: G21; G28; I22; O16; 330; financial inclusion; financial literacy; regulation; Armenia